Conserving the common heritage of humankind – Options for the deep-seabed mining regime. (April 2017) - Jaeckel, Aline; Gjerde, Kristina M.; Ardron, Jeff A.
Abstract: The seabed in areas beyond national jurisdiction is the common heritage of mankind (CHM), as declared in the 1982 United Nations Convention on the Law of the Sea. The CHM principle requires not only the sharing of benefits (the subject of a parallel article by the authors) but also the conservation and preservation of natural and biological resources for both present and future generations. The International Seabed Authority, tasked with operationalising the CHM principle in the context of deep-seabed mining, has not yet defined which measures it will take to give effect to environmental aspects of the CHM principle. This article seeks to contribute to the discussion about the operationalization of the CHM principle by specifically examining the environmental dimension of the CHM principle. To this end, the article interprets the CHM principle in the context of sustainable development and discusses a number of potential options the Authority could consider to support the application of the CHM principle. These include: funding scientific research to increase knowledge about the deep ocean for humankind; ensuring public participation in the decision-making process; debating the need for and alternatives to deep-seabed mining; determining conservation targets and levels of harm deemed acceptable; limiting environmental impacts; preserving mineable sites for future generations; compensating humankind for environmental harm; and ensuring enforcement. Highlights: The aims of the common heritage of mankind principle include environmental protection. The principle is linked to sustainable development and intergenerational equity. Operationalising the principle for deep seabed mining will require actions such as: taking a long-term perspective considering all stakeholders and future generations and establishing conservation targets that reflect best scientific knowledge.